2017
DOI: 10.1038/tp.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

The CACNA1C risk allele rs1006737 is associated with age-related prefrontal cortical thinning in bipolar I disorder

Abstract: Calcium channels control the inflow of calcium ions into cells and are involved in diverse cellular functions. The CACNA1C gene polymorphism rs1006737 A allele has been strongly associated with increased risk for bipolar disorder (BD) and with modulation of brain morphology. The medial prefrontal cortex (mPFC) has been widely associated with mood regulation in BD, but the role of this CACNA1C polymorphism in mPFC morphology and brain aging has yet to be elucidated. One hundred seventeen euthymic BD type I subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 78 publications
1
17
1
1
Order By: Relevance
“…According to our analysis, the right prefrontal cortical thickness of our patients was related to mood stabilizers and was not significantly associated with the presence of the CACNA1C risk A allele rs1006737. These results are discordant to previous works, where the presence of this risk allele relates to increased GM density and cortical thickness 12,18,37 even in healthy subjects. 13 There are two characteristics of our study that might explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…According to our analysis, the right prefrontal cortical thickness of our patients was related to mood stabilizers and was not significantly associated with the presence of the CACNA1C risk A allele rs1006737. These results are discordant to previous works, where the presence of this risk allele relates to increased GM density and cortical thickness 12,18,37 even in healthy subjects. 13 There are two characteristics of our study that might explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 77%
“…12,17 A recent analysis of 117 BD Brazilian patients associated the risk A allele with greater cortical thickness measures in PFC. 18 However, these studies used heterogenic samples that included patients treated with different medications which are a known cause of brain morphometric changes. 9 Among the treatments for BD, mood stabilizers are medications with antimanic, antidepressant and prophylactic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ca v 1.2 channels are widely expressed in dendrites and spines, where they regulate calcium entry 118 . Brain imaging studies have found that the CACNA1C risk allele is associated with an age-related prefrontal cortical thinning in individuals with bipolar disorder 119 . Activity-dependent pruning of the excitatory synapses of medium spiny neurons is dependent on Ca 2+ entry through Ca v 1.2 in co-culture models, indicating that pruning may play a part in this age-related thinning 120 .…”
Section: Genetic Risk and Structural Plasticitymentioning
confidence: 99%
“…These intermediate phenotypes are assumed to involve the same biological pathways as the illness but to relate more closely to the effects of relevant genes [61-65]. Recent studies of several psychiatric candidate genes including ZNF804A [66-68] and CACNA1C [69-72] have already demonstrated the validity and reliability of this approach. We previously also analyzed the association between VRK2 SNPs and brain phenotypes related to psychiatric disorders [34] and found that the psychiatric risk allele [C] in rs2312147 was associated with reduced total brain volume and white matter volume in healthy individuals, which was in line with clinical characteristics in the brains of psychiatric patients compared with healthy controls [73].…”
Section: Identification Of Vrk2 Variants In Psychiatric Disorders Amomentioning
confidence: 99%